Titik Temu antara Ekonomi Islam, Kearifan, dan Budaya Lokal - Samsul Mu’arif (AL-BURHAN, 2022)
An economic system based on the cultural customs of the archipelago is one of the local wisdom assets of the pluralistic Indonesian nation. There is a slight difference between local wisdom and local culture because both have unique characteristics. Wisdom presents the community's perspective on issues based on high values, while local culture is more directed to the product of habits that have been practiced by the community for generations. Some values of local wisdom and local culture that are in accordance with the field of Islamic economics include the values of justice and honesty, the value of helping and siding with the weak, the value of professionalism. Characteristics and values that have been rooted in have proven to have maintained the economy in shaping Indonesian society for the better. Even after the entry of Islam, cultural values and local wisdom continued to grow sustainably without any difference with Islamic economic values.